2015
DOI: 10.6060/mhc150662k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of poly-Phenylporphyrin Film Activated by Superoxide Anion Radical

Abstract: Электрохимической полимеризацией получены пленки поли-5,10,15,20-тетракис(4'-аминофенил) 10,15,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In order to degas or oxygenate solutions before the electrochemical measurements, argon or oxygen was bubbled through the capillary tube for 30 min. In earlier paper we have shown that in DMSO media the more effective electrochemical deposition of polyporphyrin films was obtained under activation by oxygen [31,32]. Therefore, in this paper the polyporphyrin films deposition included cycling of the working electrode potential in the oxygenated solutions (to activate the deposition process), then cycling in degassed solutions (to stabilize the resulting film).…”
Section: Methodsmentioning
confidence: 99%
“…In order to degas or oxygenate solutions before the electrochemical measurements, argon or oxygen was bubbled through the capillary tube for 30 min. In earlier paper we have shown that in DMSO media the more effective electrochemical deposition of polyporphyrin films was obtained under activation by oxygen [31,32]. Therefore, in this paper the polyporphyrin films deposition included cycling of the working electrode potential in the oxygenated solutions (to activate the deposition process), then cycling in degassed solutions (to stabilize the resulting film).…”
Section: Methodsmentioning
confidence: 99%
“…4−8 The aggregation of photosensitizers could enhance the transfer of electrons produced by photosensitizers under illumination and further increase the production of superoxide anions (O 2 − ). 9,10 The O 2 − has low or less toxicity to tumor cells because it could be eliminated by superoxide dismutase (SOD). 11−15 Meanwhile, the aggregation of photosensitizers could also increase nonradiative transitions of photosensitizers (relaxation vibration, internal transitions, and intersystem transitions), and their absorbed light energy is released in the form of heat.…”
Section: Introductionmentioning
confidence: 99%